Transcriptomic and de novo proteomic analyses of organotypic entorhino-hippocampal tissue cultures reveal changes in metabolic and signaling regulators in TTX-induced synaptic plasticity - Maximilian Lenz; Paul Turko; Pia Kruse; Amelie Eichler; Zhuo Angel Chen; Juri Rappsilber; Imre Vida; Andreas Vlachos (Molecular Brain)
Abstract Understanding the mechanisms of synaptic plasticity is crucial for elucidating how the brain adapts to internal and external stimuli. A key objective of plasticity is maintaining physiological activity states during perturbations by adjusting synaptic transmission through negative feedback mechanisms. However, identifying and characterizing novel molecular targets orchestrating synaptic plasticity remains a significant challenge. This study investigated the effects of tetrodotoxin (TTX)-induced synaptic plasticity within organotypic entorhino-hippocampal tissue cultures, offering insights into the functional, transcriptomic, and proteomic changes associated with network inhibition via voltage-gated sodium channel blockade. Our experiments demonstrate that TTX treatment induces substantial functional plasticity of excitatory synapses, as evidenced by increased miniature excitatory postsynaptic current (mEPSC) amplitudes and frequencies in both dentate granule cells and CA1 pyramidal neurons. Correlating transcriptomic and proteomic data, we identified novel targets for future research into homeostatic plasticity, including cytoglobin, SLIT-ROBO Rho GTPase Activating Protein 3, Transferrin receptor, and 3-Hydroxy-3-Methylglutaryl-CoA Synthase 1. These data provide a valuable resource for future studies aiming to understand the orchestration of homeostatic plasticity by metabolic pathways in distinct cell types of the central nervous system.